The Role of Family and Religion in the Local Politics of early Elizabethan England: The Case of Hampshire in the 1560s - Fritze, Ronald H. (The historical journal, 1982)
Factionalism among the nobility and gentry was a common although by no means universal phenomenon of local politics in Tudor England. During the 1560s it was the foremost fact in the political life of Hampshire. Co-operation among the gentry is at least as significant a phenomenon for the historian as conflict. At the same time conflict is much more likely to have left documen tation. The amiable resolution of local issues would usually be celebrated by silence while a dispute was likely to culminate in a lawsuit. For Hampshire in the 1560s the survival of one of the earliest and most fully preserved disputed election cases in Star Chamber from the reign of Elizabeth provides crucial evidence of the occurrence of conflict and the motivations of the participants. Thanks to the existence of this material, which includes lists of voters for both sides, the members of both factions are clearly identified. In addition the local issues at stake are further clarified. As a result all of the evidence surviving for the entire decade can be tied together to produce a comprehensive picture of the local political situation in Hampshire.